Barriers and facilitators to COVID-19 testing and vaccination: a qualitative focus group study among Rhode Island’s Latine/Hispanic community - D. Grace Smith; Yovanska Duarte-Velez; Yovanska Duarte-Velez; Elizabeth S. Chen; Elizabeth S. Chen; Mario Bueno; A. Rani Elwy; A. Rani Elwy; Indra Neil Sarkar; Indra Neil Sarkar; Indra Neil Sarkar (Frontiers in Health Services, 2025)
IntroductionDue to a combination of cultural, situational, social, and environmental factors, members of the Latine/Hispanic community experienced higher contagion and poorer outcomes amid the COVID-19 pandemic, and lower rates of testing and vaccination. Our aims were to use the frameworks of implementation science to identify barriers and facilitators impacting equitable access to COVID-19 testing and vaccination programs among Rhode Island's (RI's) Latine/Hispanic community.MethodsBetween February and June 2021, we implemented a community-centered approach, empowering Promatoras, trusted community health leaders, to conduct eight focus groups among RI's Latine/Hispanic community (n = 55). To gain the perspectives of health delivery experts, we conducted six one-on-one interviews with healthcare professionals serving this community. Recordings were translated into English as applicable, transcribed, and analyzed using directed content analysis and thematic analysis, guided by theories of implementation science.ResultsLatine/Hispanic community members made decisions about participation in testing and vaccination programs by considering factors primarily related to their communal, religious, interpersonal, and emotional contexts. The amount and sources of information they received, perceived accessibility of interventions, and their perceived agency (i.e., freedom to decide how/when/where to follow interventions) also shaped decisions. Many barriers identified by clinicians (e.g., structural determinants to access) were not discussed by Latine/Hispanic community members.DiscussionFacilitators and barriers to test/vaccine implementation were shaped by local communal and individual factors, generally supporting previous arguments on implementation among Latine/Hispanic communities, and revealing the importance of context-specific examinations. In public health pandemic preparedness work, we encourage community-based participatory approaches to identify priorities/barriers and involvement of community leaders to build trust, frame messaging, and disseminate information.